Оптический пробой и транспортные свойства канала высокоэнергетичного пучка - Баландин С. Ф.; Копытин Ю. Д.; Тихомиров И. А. Иван Арсентьевич; Хан В. А. Валерий Алексеевич (Томск, 1987)
Деп. в ВИНИТИ 28.10.87, № 7561-В87